The European security and idense indetity (ESDI) and Turkey - Yurdakul, Halim (My University, 2002)
The goal of this study is, to examine in frame of Turkey's security interests, the security dilemma which appeared in the new World order after the Soviet Union collapsed. Within this new context, it evaluates how Turkey will provide its own security and what it should do to take part in the occurring by way of analyzing NATO and the European Security and Defense Identity built up in NATO and followed by the European Security and Defense Policy occurring in the EU. During the Cold War, the countries, which had been providing their security needs in the bi-polar, had new security search after the end of the Cold War. Turkey was one of them. Following the devise of Warsaw Pact NATO was being regarded to be abolished in the future. So was the ESDI built up in NATO. The ESDI's main mission was to fulfill so called Petersberg Tasks and in order to do this it had the opportunity to access NATO capabilities. But, as seen in Bosnia and Kosovo crisis, European allies had difficulties in participating in the operations and in gathering military troops together. After the difficulties experienced in those crisis, it is decided that the ESDI built up in NATO will be developed with the name ESDP in the EU. But it was also decided to continue accessing NATO capabilities until The ESDP can fulfill the tasks mentioned before. Turkey which firstly was thinking positively by accessing NATO capabilities by the ESDP, declared to vote it in NATO because Turkey was about to loose the rights gained before in the WEU because the ESDP was occurring in the EU and Turkey was not an EU member. Nowadays, this problem is almost over in favor of Turkey. It is conspicuous that the ESDP occurring in the EU can reach the desired level a long time because of these reasons below: (i) NATO and the EU have capabilities gap (ii)There are some problems for the European states, which are not EU member, to take part in the system. However, for Turkey, it is being evaluated, in respect of NATO's future, that the best option for Turkey is to take part in the ESDP and to guarantee this, to become a member of the EU.

Bu çalışmanın amacı, Sovyetler Birliğinin dağılmasıyla meydana gelen yeni dünya düzeninde ortaya çıkan güvenlik sorununu Türkiye açısından incelemektir.Bu bağlamda NATO ve onun içinde oluşturulan Avrupa Güvenlik ve Savunma Kimliğinin ardından bunun AB içinde Avrupa Güvenlik ve Savunma Politikasını analiz ederek Türkiye'nin güvenlik ihtiyacını nasıl karşılayacağını, bu oluşumda yer almak için neler yapması gerektiğini değerlendirmektir. Soğuk savaş yıllarındaki iki kutuplu dünya düzeninde kutuplardan birinin şemsiyesi altında bulunarak güvenlik ihtiyacını karşılayan ülkeler soğuk savaşın sona ermesiyle yeni güvenlik arayışlarına giriştiler. Türkiye'de bu ülkelerden biriydi. Varşova Paktının dağılması ile birlikte üstlenmiş olduğu görevi farklılaşmaya başlayan NATO'nun zaman içinde AGSK oluşturuldu. Bu oluşumla birlikte Petersberg Görevleri olarak adlandırılan görevleri yapacak duruma gelmek için NATO imkan ve kabiliyetlerinden faydalanacaklardır. Fakat Bosna ve Kosova krizlerinde görüldü ki Avrupa müttefikler krizlere müdahale edecek operasyonlara katılma ve kuvvetleri bir araya getirmede zaafiyet yaşamaktadırlar. Görülen bu zaafiyetler üzerine NATO içinde oluşturulmakta olan AGSK'nın, Avrupa Güvenlik ve Savunma Politikası adı altında AB içinde oluşturulmasına fakat bahsi geçen görevleri yerine getirecek yeteneğe ulaşana kadar yine NATO imkan ve kabiliyetlerinden faydalanmasına karar verildi. Önceleri NATO'nun imkanlarından faydalanmasına sıcak bakan Türkiye yeni oluşumun AB bünyesine kayması ile BAB' da kazanmış olduğu hakların elinden gitmesi yani karar alma mekanizmalarında bulunmaması nedeniyle NATO içinde veto hakkını başlarda kullanacağını açıklamış fakat sonradan bu sorun hemen hemen Türkiye'nin istekleri doğrultusunda hallolmuştur. AB içinde oluşturulmakta olan AGSP'nin gerek kendi gerekse NATO imkanlarındaki zaafiyet ve AB dışında kalan diğer Avrupalı ülkelerin sistemine dahil edilmesindeki zorluklardan dolayı epeyce bir süre istenilen seviyeye gelemeyeceği açıktır. Fakat Türkiye için, NATO'nun da geleceğini göz önünde bulundurduğumuzda en iyi güvenlik seçeneğinin AGSP içinde yer almak, onu da sağlama almak içinde AB'nin bir üyesi olmak olduğu değerlendirilmektedir.
Keywords: Güvenlik_Avrupa_Türkiye